Macroeconomic Management for Poverty Reduction : Chad, Mali, Niger - Garba, Abdoulahi; Beguy, Olivier; Kaho, Arsene; Mansour, Wael; Razafimandimby, Luc; Dessus, Sebastien (World Bank, Washington, DC, 2016)
The three countries covered in this first report, Mali, Chad and Niger, share a number of common characteristics and face a similar set of challenges, which provides the foundation for this joint-review approach. All three are low-income landlocked economies. Each relies heavily on the agricultural sector as its primary source of income and livelihoods, and each has a large livestock subsector that is based in part on traditional nomadic pastoralism. All countries have important natural resource industries, gold for Mali, uranium and oil for Niger, and oil for Chad, which represent the bulk of export earnings and public revenue. This dependence on the primary sector renders these economies highly vulnerable to weather-related shocks and volatile commodity prices. Each is struggling to overcome a legacy of instability and violence, which is complicated both by the fragility of domestic socio-political conditions and the severity of regional security challenges. Finally, all three countries are members of a monetary union that uses a regional currency pegged to the euro and exercises significant influence over the macroeconomic policies of its member states. At the center of the trade-off between stabilization and development lies public investment management, at macroeconomic and financial management levels. Faced with repeated negative shocks, countries tend to cut ongoing and planned public investment projects which are often designed to reduce drivers of fragility and strengthen the resilience of economies, thus perpetuating risks of falling into fragility traps. Hence, Section three discusses the impact of public investment volatility on its quality in Chad, Mali and Niger, and explores possible options in terms of macroeconomic and public financial management to smooth public investment budget execution.